Catastrophic co-production: A student-staff partnership for developing an educational game - Glover, Nicholas; Knox, Kerry J.; Kirman, Ben; Topham, Matthew; Westbury-Hawkins, Katylily; Holland, Penelope (International Journal for Students as Partners, 2020)
We describe the production of an educational game (Catastrophic) for supporting biology learning in higher education (HE) that was developed through a partnership between students and academic staff. We consider the ways in which the development project intersects with the use of game-based learning in HE and with Students as Partners (SaP) practice. We describe the rationale for the project, discussing the use of games in the context of a shift from surface to deep learning during the transition to HE. We then reflect upon the development process and the resulting game, drawing on student and staff perspectives gathered using interviews. Finally, we make recommendations for others embarking on student-staff partnerships for the co-creation of teaching and learning tools.